2016
DOI: 10.1097/md.0000000000005193
|View full text |Cite
|
Sign up to set email alerts
|

Alternation of regional homogeneity in trigeminal neuralgia after percutaneous radiofrequency thermocoagulation

Abstract: We used resting-state fMRI to investigate regional homogeneity (ReHo) changes in patients with TN before and after PRT procedure, and to speculate about its possible mechanisms.Thirty-one TN patients underwent the PRT procedure had MRI scans just before and 6 months after surgery. The anatomical and resting-state functional images were all acquired. Patients’ visual analog scales (VAS) scores, facial numbness, and disease duration were also recorded. Voxel-wise ReHo analysis was performed to detect the altered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…The postcentral gyrus is the somatosensory cortex, which is highly connected to other areas of the brain (58) and has numerous functions, including representation of the body, tactile attention, sensorimotor integration, and others (59). The reduced ReHo of the postcentral gyrus may be involved in pain processing, as patients with EMTB could experience persistent pain of the lesions in a clinical setting (1,60), which is supported by several studies on acute eye pain (61), low back pain (62), and trigeminal neuralgia (63). Furthermore, studies on the amplitude of low-frequency fluctuation (ALFF) also support the relevance of persistent pain to the postcentral gyrus (64,65).…”
Section: Discussionmentioning
confidence: 91%
“…The postcentral gyrus is the somatosensory cortex, which is highly connected to other areas of the brain (58) and has numerous functions, including representation of the body, tactile attention, sensorimotor integration, and others (59). The reduced ReHo of the postcentral gyrus may be involved in pain processing, as patients with EMTB could experience persistent pain of the lesions in a clinical setting (1,60), which is supported by several studies on acute eye pain (61), low back pain (62), and trigeminal neuralgia (63). Furthermore, studies on the amplitude of low-frequency fluctuation (ALFF) also support the relevance of persistent pain to the postcentral gyrus (64,65).…”
Section: Discussionmentioning
confidence: 91%
“…One of our previous studies using dynamic regional homogeneity has shown that TN is associated with abnormal brain function in the pre-central gyrus and middle temporal gyrus ( Yan et al, 2019 ). Moreover, a regional homogeneity study in patients with TN after percutaneous RF thermo coagulation has shown alternations in the right middle temporal gyrus, right calcarine, and left post-central gyrus, which may be related to sensory, affective, and emotional processes ( Dou et al, 2016 ). The observed patterns of decreased rCBF brain regions using a more liberal threshold of P < 0.001 (uncorrected) support functional and structural changes in chronic pain from previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, fMRI technology may provide us with qualitative and quantitative observations [76]. For example, PoCG's corresponding somatosensory representative area can help clinicians determine the pain site, and the degree of activation can also reflect the intensity of pain [51]. The local activity consistency of rostralanterior part of ACC in patients with postherpetic neuralgia was significantly correlated with the anxiety and depression scores [77,78].…”
Section: The Value Of Fmri In the Clinical Treatment Of Neuropathic Painmentioning
confidence: 99%